Mechanistic insight of curcumin: a potential pharmacological candidate for epilepsy - Khatoon, Saima; Kalam, Nida (Frontiers in Pharmacology, 2025)
Recurrent spontaneous seizures with an extended epileptic discharge are the hallmarks of epilepsy. At present, there are several available anti-epileptic drugs (AEDs) in the market. Still no adequate treatment for epilepsy treatment is available. The main disadvantages of AEDs are their associated adverse effects. It is a challenge to develop new therapies that can reduce seizures by modulating the underlying mechanisms with no adverse effects. In the last decade, the neuromodulatory potential of phytoconstituents has sparked their usage in the treatment of central nervous system disorders. Curcumin is an active polyphenolic component that interacts at cellular and molecular levels. Curcumin’s neuroprotective properties have been discovered in recent preclinical and clinical studies due to its immunomodulatory effects. Curcumin has the propensity to modulate signaling pathways involved in cell survival and manage oxidative stress, apoptosis, and inflammatory mechanisms. Further, curcumin can persuade epigenetic alterations, including histone modifications (acetylation/deacetylation), which are the changes responsible for the altered expression of genes facilitating the process of epileptogenesis. The bioavailability of curcumin in the brain is a concern that needs to be tackled. Therefore, nanonization has emerged as a novel drug delivery system to enhance the pharmacokinetics of curcumin. In the present review, we reviewed curcumin’s modulatory effects on potential biomarkers involved in epileptogenesis including dendritic cells, T cell subsets, cytokines, chemokines, apoptosis mediators, antioxidant mechanisms, and cognition impairment. Also, we have discussed the nanocarrier systems for encapsulating curcumin, offering a promising approach to enhance bioavailability of curcumin.